Alpha Wave Activity on Think Hard and Dhikr Condition Using Electroencephalographic (EEG) - Huwaidah, Indah Rifdah; Kholidah, Kholidah; Sumarti, Heni (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
Emotions are very important in thinking, making decisions, and a person's personality. This research was conducted to know the activity of alpha waves using an electroencephalographic (EEG) instrument, using an experimental method given the treatment of thinking hard and dhikr of istighfar. The brain waves analyzed in this study are alpha waves with a frequency between 8-12 Hz. The analysis shows that the alpha wave mean result is 11.89 Hz when thinking hard, and the mean result is 10.89 Hz during dhikr. The statistical test results show a significance of p = 0.000323 (p < 0.05), showing that dhikr can volunteer from a state of hard thinking to a relaxed state. The istighfar dhikr (astaghfirullah hal adzim) by the volunteer is a response to ask for forgiveness and reassure the heart.